Study of the effect of high-energy discrete processing on the extraction kinetics and properties of wool grease - Semeshko, Olga; Kunik, Alexandra; Asaulyuk, Tatiana; Saribyekova, Yulia; Myasnykov, Sergey (Eastern-European Journal of Enterprise Technologies, 2016)
Wool grease is a valuable raw material for the food, perfume and cosmetic and pharmaceutical industries. The extraction method is selected for wool grease extraction, which will allow extracting the maximum amount of it, but for a long time. The use of high-energy discrete processing as a method of preliminary processing of wool fibers to accelerate the wool grease extraction is proposed. The effect of the proposed intensification method on the wool grease extraction kinetics is investigated. It is found that the high-speed discrete processing increases the wool grease extraction rate, as evidenced by an increase in the reaction rate constant. The changes in the basic physical and chemical properties of the resulting wool grease under the influence of high-energy discrete processing are examined. It is determined that high-energy discrete processing enhances the wool grease quality. The mechanism of the intensifying effect of preliminary high-energy discrete processing of wool fibers on the wool grease extraction process is proposed.